Microstepping Drives Approaches to Improve Machine Carriage/ Conveyor Movement - Addie Irawan, Hashim; M. F., Abas; A., Hazha; N. H., Nordin (2008)
Due to the microstepping advantages, the research and development has been done to provide better technique and signal processing for microstepping drives for each type of stepper motor. This article will discuss on experiment on two techniques to provide microstepping for bipolar stepper motor. The study is focused on controlling microstepping using two methods; “ON”,“OFF” delay control signal (ODC) and “ON”,”OFF” with pulse width modulation control (OPWMC) signal. The purpose of the study is to improve the movement of the conveyor or carriage part of a machine which is driven by a bipolar stepper motor. The experiment is done on the carriage movement control with two type of driving style; direct winding control (DWC) and conductive control (CC). The performance is referred from the distance movement (axis) of the carriage machine (left right/rightleft). The results are show that the DWC with OPWMC technique give more precise movement from CC with ODC and DWC without OPWMC technique to correct the distance movement error and reducing the resonance occurred during stepper motor drives.